Cochrane Database of Systematic Reviews 2007
DOI: 10.1002/14651858.cd003843.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Bispectral index for improving anaesthetic delivery and postoperative recovery

Abstract: Anaesthesia guided by BIS within the recommended range (40 to 60) could improve anaesthetic delivery and postoperative recovery from relatively deep anaesthesia. In addition, BIS-guided anaesthesia has a significant impact on reduction of the incidence of intraoperative recall in surgical patients with high risk of awareness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(40 citation statements)
references
References 47 publications
0
35
0
1
Order By: Relevance
“…We used the BIS to monitor the depth of anesthesia which provides a continuous age-independent monitoring of hypnotic state induced by the most widely used sedative-hypnotic agent and has been used to assess the induction quality, depth of anesthesia, intraoperative requirement of anesthetics, and to reduce the incidence of intraoperative recall and awareness. [811] Doi et al . studied the relationship between calculated blood concentration of propofol and electrophysiological variables (BIS, 95% SEF, median frequency, and auditory evoked potential index) during emergence from anesthesia and concluded that blood concentration of propofol best correlates with BIS value.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used the BIS to monitor the depth of anesthesia which provides a continuous age-independent monitoring of hypnotic state induced by the most widely used sedative-hypnotic agent and has been used to assess the induction quality, depth of anesthesia, intraoperative requirement of anesthetics, and to reduce the incidence of intraoperative recall and awareness. [811] Doi et al . studied the relationship between calculated blood concentration of propofol and electrophysiological variables (BIS, 95% SEF, median frequency, and auditory evoked potential index) during emergence from anesthesia and concluded that blood concentration of propofol best correlates with BIS value.…”
Section: Discussionmentioning
confidence: 99%
“…[7] Bispectral index (BIS) provides a continuous age-independent monitoring of hypnotic state induced by the most widely used sedative-hypnotic agent and has been used to assess the induction quality, depth of anesthesia, intraoperative requirement of anesthetics, postoperative recovery, and to reduce the incidence of intraoperative recall awareness. [811] BIS value of 0 represents an isoelectric electroencephalogram and 100 represents an awake state, whereas 40 to 60 reflect adequate hypnotic effect for general anesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are questions regarding the efficacy for the use of a bispectral index (BIS) monitor while providing OBA [13,17]. Of interest is a recent Cochrane collaboration review completed by Punjasawadwong et al [18 ], in an effort to assess whether BIS reduced anesthesia use, recovery times, recall awareness and costs. They found that BIS-guided anesthesia reduced the requirement of propofol by 1.3 mg/kg/h for ambulatory gastrointestinal procedures.…”
Section: Monitoringmentioning
confidence: 99%
“…Intraoperative monitoring of the depth of anesthetic is important to prevent this problem. Use of the bispectral index (BIS) reduces the cases of intraoperative awareness [2,3,4]. The BIS is a single number calculated from electroencephalogram (EEG)-derived sub-parameters.…”
Section: Introductionmentioning
confidence: 99%